How is agile development currently being used in regulated embedded domains?. Issue 8 (22nd January 2018) - Diebold, Philipp; Theobald, Sven
Abstract: Background: Agile development shows benefits for software‐developing companies, eg, shorter time to market or stronger customer connections. Nonetheless, agile methods and practices are most often adapted to a specific context. Especially in regulated domains such as automotive, avionics, or medical, domain‐specific constraints need to be considered, and hence, Agile is often used only partially or not at all. Objective: The goal of this study was to identify the state of the practice in using agile development as part of the development process in regulated embedded domains. Method: We conducted a study using a combination of a series of interviews and an online questionnaire as data collection methods. Results: The responses of 50 participants showed that Agile, mostly in the form of an adapted form of Scrum, has already arrived in those domains, but mainly in noncritical projects and/or early project phases. This means there is further improvement potential, which was also confirmed by the participants regarding future usage. Conclusions: The results of our state‐of‐the‐practice study provide a good stage for future work, especially for new approaches bringing more "agility" into regulated embedded domains.